RALPH WALDO EMERSON’S PRINCIPLE ON ENVIRONMENTAL ETHICS - Fuad Hasyim (Lire Journal (Journal of Linguistics and Literature), 2021)
This paper aims at examining Ralph Waldo Emerson’s view on the principle of environmental ethics as reflected in his essay entitled “Nature.” The study of this research applied to content analysis. The writer intended to explore, understand and capture the messages of the work art. So, the writer built explored conception (environmental ethics) before coming into a work of art. The main result displayed six environmental ethics: respecting nature, cosmic solidarity, love and caring for nature, no harm, simplicity and harmony life with nature, and moral integrity. It is concluded that Emerson’s work has reflected the author’s care on the American social context of the 18th century at the era of industrialization that exploited their environment to enlarge their economic development